Beyond the Screen and Page: Understanding Teachers’ Lived Experiences with Artificial Intelligence in Education - Ubagan, Diana Rose (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study aimed to explore teachers’ lived experiences in integrating Artificial Intelligence (AI) in education, focusing on their perceptions, challenges, and pedagogical implications. Anchored in phenomenology and guided by the Technological Pedagogical Content Knowledge (TPACK) framework and social constructivism theory, the study examined how teachers interpret and utilize AI in teaching practices. A qualitative research design was employed using semi-structured one-on-one interviews with six English teachers from Don Carlos Polytechnic College selected through purposive sampling. Data were analyzed using Braun and Clarke’s thematic analysis to identify patterns and themes. The findings revealed four major themes: relief with risk, teachers’ authority, motion in pedagogy, and structures that shape and constrain possibility. Teachers experienced AI as a tool that enhances efficiency and reduces workload but requires careful validation due to concerns about inaccuracy and overreliance. They emphasized their irreplaceable role in ensuring ethical use, maintaining academic integrity, and guiding authentic learning. AI also emerged as a catalyst for pedagogical innovation, supporting creativity and productivity; however, its effectiveness is constrained by infrastructural limitations, unequal access, and lack of institutional support. The results further showed that AI integration involves a balance between opportunities and constraints, with teachers actively exercising professional judgment and adapting AI tools within their contexts. The study concludes that effective AI integration depends on teachers’ critical awareness, ethical responsibility, and institutional support systems. It recommends further research on AI reliability, teacher training, policy development, and equitable access to technology. This study aligns with SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 9 (Industry, Innovation and Infrastructure) by promoting improved teaching practices, professional development, and technological integration in education. The findings contribute to educational, technological, and institutional sustainability by informing policy development, strengthening teacher capacity, and supporting equitable and responsible use of AI in educational systems.
Keywords: Artificial intelligence; Educational sustainability; Phenomenology; Teachers’ perceptions; Teaching practices; Technological Pedagogical Content Knowledge (TPACK); Thematic analysis